2009
DOI: 10.1161/hypertensionaha.108.123455
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Approach to the Treatment of Uncomplicated Hypertension

Abstract: Abstract-Notwithstanding the availability of antihypertensive drugs and practice guidelines, blood pressure control remains suboptimal. The complexity of current treatment guidelines may contribute to this problem. To determine whether a simplified treatment algorithm is more effective than guideline-based management, we studied 45 family practices in southwestern Ontario, Canada, using a cluster randomization trial comparing the simplified treatment algorithm with the Canadian Hypertension Education Program g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
152
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(172 citation statements)
references
References 20 publications
(23 reference statements)
10
152
0
10
Order By: Relevance
“…4,23 Initiating treatment with dual combination therapy has 272 been advocated 24 as a more effective means to achieve BP control rapidly and with fewer clinical visits. 25 …”
mentioning
confidence: 99%
“…4,23 Initiating treatment with dual combination therapy has 272 been advocated 24 as a more effective means to achieve BP control rapidly and with fewer clinical visits. 25 …”
mentioning
confidence: 99%
“…Certainly, there is much to be said for simplicity. In one study, a simplification of hypertension treatment into an abridged algorithm allowed more uncomplicated patients to reach blood pressure targets than using CPG-based practice 32 . It must be acknowledged, however, that to ignore preference studies would result in the systematic exclusion of one class of relevant evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Information obtained from these analyses are of potential clinical relevance, since they can be effectively implemented by recommendations derived from international guidelines, in order to improve the clinical management and achieve the recommended blood pressure targets. In particular, recent studies have demonstrated that the implementation of rational and effective therapeutic regimes, mostly based on combination therapies, may promote higher rates of blood pressure control also in the setting of real practice [5][6][7].In this issue of High Blood Pressure and Cardiovascular Prevention, Kiselev and co-authors reported a detailed and comprehensive analysis of clinical factors that may have potential impact on the achievement of the blood pressure goals in a large sample of adult individuals with hypertension in the Ivanovo, Russia [8]. This study is part of the larger Russian Registry of Hypertension, Coronary Artery Disease and Chronic Heart Failure, which is a retrospective, continuous, nation-wide, web-based registry.…”
mentioning
confidence: 99%
“…Information obtained from these analyses are of potential clinical relevance, since they can be effectively implemented by recommendations derived from international guidelines, in order to improve the clinical management and achieve the recommended blood pressure targets. In particular, recent studies have demonstrated that the implementation of rational and effective therapeutic regimes, mostly based on combination therapies, may promote higher rates of blood pressure control also in the setting of real practice [5][6][7].…”
mentioning
confidence: 99%